2014
DOI: 10.1681/asn.2013091028
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Methicillin-Resistant Staphylococcus aureus Colonization and Risk of Infection in Dialysis Patients

Abstract: Patients undergoing dialysis are particularly vulnerable to methicillin-resistant Staphylococcus aureus (MRSA) infections. We performed a meta-analysis of published studies to estimate the prevalence of MRSA colonization in dialysis patients, time trends, and long-term risk of subsequent MRSA infections. Our search of the PubMed and Embase databases returned 5743 nonduplicate citations, from which we identified 38 relevant studies that included data on 5596 dialysis patients. The estimated prevalence of MRSA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 76 publications
3
50
3
Order By: Relevance
“…One first finding from this study is the high prevalence of MRSA and VRE colonization even before transplantation. The observed prevalence of MRSA colonization in the transplant setting is comparable with the estimated MRSA carriage of other high-risk populations, such as patients on hemodialysis (7.2%, 95% CI 4.9%-9.9%) (39) and patients admitted to the ICU (7.0%, 95% CI 5.8%-8.3%) (4). The risk of VRE colonization also shows similarity to that observed in the ICU setting (8.8%, 95% CI 7.1%-10.6%) (5).…”
Section: Discussionsupporting
confidence: 52%
“…One first finding from this study is the high prevalence of MRSA and VRE colonization even before transplantation. The observed prevalence of MRSA colonization in the transplant setting is comparable with the estimated MRSA carriage of other high-risk populations, such as patients on hemodialysis (7.2%, 95% CI 4.9%-9.9%) (39) and patients admitted to the ICU (7.0%, 95% CI 5.8%-8.3%) (4). The risk of VRE colonization also shows similarity to that observed in the ICU setting (8.8%, 95% CI 7.1%-10.6%) (5).…”
Section: Discussionsupporting
confidence: 52%
“…However, there are important ways in which home HD differs from in-center HD that may substantially alter the risks associated with CVC use. Patients undergoing in-center HD have three times per week exposure to dialysis facilities, in which they come into contact with other chronically ill patients as well as facility staff members, presenting opportunities for exposure to exogenous organisms, including multidrug-resistant organisms (23)(24)(25). Although rates of colonization with multidrugresistant organisms are unknown in patients undergoing home HD, it is plausible that less frequent contact with health care facilities would result in less frequent colonization and infection.…”
Section: Discussionmentioning
confidence: 99%
“…MRSA colonization in hemodialysis patients has been associated with a higher subsequent risk of infection and bacteremia [8] and a 2.46-fold higher risk of all-cause mortality [9]. Patel et al reported that 17.6% of patients colonized with MRSA subsequently developed a clinical infection [3].…”
Section: Tablementioning
confidence: 99%
“…Patel et al reported that 17.6% of patients colonized with MRSA subsequently developed a clinical infection [3]. Likewise, a recent meta-analysis reported that 19% of hemodialysis patients with MRSA colonization developed a clinical MRSA infection within 6-20 months [8]. …”
Section: Tablementioning
confidence: 99%